Analisis Peran Mahasiswa dalam Meningkatkan Efektivitas Tim Kerja di Lingkungan Magang (Studi Kasus KPP Pratama Pasuruan) - Mauliddiva, Aziza; Maulana, Moh Irham; Bakhri, Saiful (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to analyze the role of interns in improving team effectiveness in an internship environment, with a case study at KPP Pratama Pasuruan. The internship program provides students the opportunity to apply the knowledge gained in university into real-world work settings, while also contributing to team performance. This research uses a qualitative approach, with data collection techniques including in-depth interviews, observations, and questionnaires with interns, internship supervisors, and team members at KPP Pratama Pasuruan. The findings show that interns contribute positively to team effectiveness through creative ideas, enhancing team morale, and assisting in operational tasks that support the team's objectives. However, the main challenges faced by interns include difficulties in adapting to organizational culture and managing expectations between interns and the company. Active mentorship and effective communication between interns and team members are key factors in supporting successful collaboration. This study recommends that companies provide more intensive guidance, assign relevant and challenging tasks, and improve interns' communication skills to maximize their contribution to team effectiveness.